2014
DOI: 10.14202/vetworld.2014.882-889
|View full text |Cite
|
Sign up to set email alerts
|

Virological and immunological studies on foot and mouth disease virus type SAT2 naturally infected and vaccinated buffalo cows and their calves

Abstract: 2014) Virological and immunological studies on foot and mouth disease virus type SAT2 naturally infected and vaccinated buffalo cows and their calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The absence of NSP antibodies in the calves in the control group ruled out subclinical infection. Following that, the titre of anti-NSP and anti-SP antibodies in these calves decreased from the 4 th to the 90 th day after birth, and similar findings were also reported by El-Sayed Ibrahim., et al [16], who reported that passively obtained colostrum antibodies had decreased to undetectable levels due to IgG's half-life of approximately 16 days [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of NSP antibodies in the calves in the control group ruled out subclinical infection. Following that, the titre of anti-NSP and anti-SP antibodies in these calves decreased from the 4 th to the 90 th day after birth, and similar findings were also reported by El-Sayed Ibrahim., et al [16], who reported that passively obtained colostrum antibodies had decreased to undetectable levels due to IgG's half-life of approximately 16 days [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of anti-NSP antibodies as well as anti-SP antibodies for FMD virus serotypes 'O,' ' A,' and ' Asia1' in these calves suggests the passive transfer of maternal antibodies via colostrum from immunised dams to their calves. Previous research has shown that maternal antibodies can survive in calves for up to two months after birth [16,17], whereas Akhter., et al [18] found MDA in calves' serum up to the age of 22-23 weeks. The immune response of newborn calves to FMDV depends on vaccine formulation and may or may not be dependent on maternal antibodies [6,7].…”
Section: Discussionmentioning
confidence: 99%